(untitled) (Research, Society and Development, 2022)
Travel Medicine is one branch of medicine which specializes in preventing and treating medical problems for travelers especially when they are traveling. It is undeniable that there are differences in medical knowledge between developing and developed countries when dealing with traveler’s health problems. The purpose of this study is to comprehend the characteristics and health problems of travelers who visited Sanglah General Hospital between 2017 and 2019. This is a descriptive study which used consecutive sampling in every medical record of the patients to study their health problems. Every medical record recorded the name, age, sex, health insurance, inpatient or outpatient, and diagnosis of the patients. As many as 618 subjects’ medical record number was conducted at first with dominantly men (55.2%) and women (44.8%). The mean age of this study was 42,76 years old with the eldest age being 92 years old and the youngest being 18 years old. As many as 328 subjects (53.1%) of this study did not use health insurance and only 290 subjects (46.9%) used health insurance. The number of outpatients, which was 564 subjects (91.3%), was much more than the number of inpatients in this study. Frequent health problems that subjects suffered were malignancy (solid and hematologic) 116 subjects (18.7%), kidney problem 107 subjects (17.3%), and accident (wounds, fracture and head trauma) 44 subjects (7.1%). Descriptive study among travelers is not usually done in our hospital and this is an elementary study so that in the future there will be more study for travelers. Keywords: Travel medicine; Travel; Tourism.